Transition radiation induced by nonrelativistic electron bunches - Bolotov, V.N.; Kononenko, S.I.; Muratov, V.I.; Fedorchenko, V.D. (Вопросы атомной науки и техники, 2009)
The experiments showed that the Bernstein – Green – Kruskal (BGK)-waves can be used to form short electron bunches
with time durations ranging between 50 and 100 ps. Experiments on generating electromagnetic pulses (EMPs) by
using nonrelativistic electron bunches passing through diaphragms of various radii and complex geometries are
described. Results obtained may also be used in designing devices for generating EMPs with tunable characteristics. Розглядається можливість генерації коротких електронних згустків тривалістю від 50 до 100 пс хвилями
Бернштейна-Гріна-Крускала (БГК) і формування електромагнітних імпульсів (ЕМІ) з керованими
характеристиками на діафрагмах різної геометрії. Експерименти продемонстрували, що БГК-хвилі можуть бути
використані для формування коротких електронних згустків з керованими характеристиками. Рассматривается возможность генерации коротких электронных сгустков протяженностью от 50 до 100 пс
волнами Бернштейна-Грина-Крускала (БГК) и формирования электромагнитных импульсов (ЭМИ) с
управляемыми характеристиками на диафрагмах разных геометрий. Эксперименты продемонстрировали, что
БГК-волны могут использоваться для формирования коротких ЭМИ с управляемыми характеристиками.